Recent advances in cell membrane-based biomimetic delivery systems for Parkinson’s disease: Perspectives and challenges - Jasleen Kaur; Abhishek Thakran; Saba Naqvi (Asian Journal of Pharmaceutical Sciences)
Neuroinflammation, α-synuclein pathology and dopaminergic cell loss are the hallmarks of Parkinson’s disease (PD), an incurable movement disorder. The presence of the blood-brain barrier (BBB) impedes the delivery of therapeutics and makes the design of drug-targeting delivery vehicles challenging. Nanomedicine is designed and has significantly impacted the scientific community. Over the last few decades, to address the shortcomings of synthetic nanoparticles, a new approach has emerged that mimic the physiological environment. Cell membrane-coated nanoparticles have been developed to interact with the physiological environment, enhance central nervous system drug delivery and mask toxic effects. Cell membranes are multifunctional, biocompatible platforms with the potential for surface modification and targeted delivery design. A synchronous design of cell membrane and nanoparticles is required for the cell membrane-based biomimetics, which can improve the BBB recognition and transport. This review summarizes the challenges in drug delivery and how cell membrane-coated nanoparticles can overcome them. Moreover, major cell membranes used in biomedical applications are discussed with a focus on PD.